2D metamaterial with in-plane positive and negative thermal expansion and thermal shearing based on interconnected alternating bimaterials. (9th October 2019) - Lim, Teik-Cheng
Abstract: A class of 2D metamaterials, in the form of cell walls made from bimaterial strips of alternating orientation and interconnected by rigid rods, is introduced herein to exhibit effective biaxial positive and negative thermal expansions. The magnitudes of the overall effective coefficients of thermal expansion (CTE) can be increased by increasing the slenderness of the bimaterial strip and CTE difference in the bimaterial. Results also indicate that the CTE in any particular axis can be adjusted by altering the aspect ratios of the cells and their arrangement. In addition to biaxial positive or negative thermal expansion, the metamaterial can also be made to exhibit thermal shearing, thereby manifesting positive and negative thermal expansion in directions diagonal to the connecting rods.